2017
DOI: 10.1016/j.clim.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-regulated STAT1 activation promotes TLR8 expression to facilitate signaling via microRNA-21 in systemic lupus erythematosus

Abstract: Recent studies implicate innate immunity to systemic lupus erythematosus (SLE) pathogenesis. Toll-like receptor (TLR)8 is estrogen-regulated and binds viral ssRNA to stimulate innate immune responses, but recent work indicates that microRNA (miR)-21 within extracellular vesicles (EVs) can also trigger this receptor. Our objective was to examine TLR8 expression/activation to better understand sex-biased responses involving TLR8 in SLE. Our data identify an estrogen response element that promotes STAT1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 51 publications
3
50
0
Order By: Relevance
“…This increase in insulin export relied on enhanced EV export, as the concentration of insulin inside the EV subtypes did not change following treatment. MiRNA may act as adjuvants in immune activation and recently six miRNA with the potential to bind directly to the TLR-7 receptor of innate immunity have been described in MV and sEV 23,24,[26][27][28]48,49 . Here we wanted to investigate how TLRbinding miRNA are sorted into EV and whether their expression in these vesicles changes in situations of stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in insulin export relied on enhanced EV export, as the concentration of insulin inside the EV subtypes did not change following treatment. MiRNA may act as adjuvants in immune activation and recently six miRNA with the potential to bind directly to the TLR-7 receptor of innate immunity have been described in MV and sEV 23,24,[26][27][28]48,49 . Here we wanted to investigate how TLRbinding miRNA are sorted into EV and whether their expression in these vesicles changes in situations of stress.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, six specific GU-rich miRNA sequences have been identified (let-7b/c, miR-21, miR-7a, miR-29a/b) that may stimulate immune signalling by binding to the Toll-like receptor-7 (TLR-7), independently of RNAi. Packed into EV, these miRNA sequences act as DAMP exacerbating inflammation in cancer, neurological and autoimmune settings [22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…The latest research shows that EVs carry specific miRNA that activate TLR8 and subsequently stimulate the innate immune system. This research describes a new inflammatory pathway for SLE . It was also reported that there are cell‐free nucleic acids present in the mother's circulation, either in the form of apoptotic bodies or as so‐called syncytiotrophoblast debris (EVs that contain RNA or DNA), during pregnancy.…”
Section: Introductionmentioning
confidence: 94%
“…This research describes a new inflammatory pathway for SLE. 93 It was also reported that there are cell-free nucleic acids present in the mother's circulation, either in the form of apoptotic bodies or as so-called syncytiotrophoblast debris (EVs that contain RNA or DNA), during pregnancy. These cell-free nucleic acids are increased during FGR as well as PE.…”
Section: Immune Response To Evs During Various Pregnancy Complicationsmentioning
confidence: 99%
“…In MCF-7 cells, MIR21 is upregulated by the ESR2 selective ligand diarylpropionitrile (DPN) [104]. In systemic lupus erythematosus, estrogen-regulated STAT1 activates and promotes TLR8 expression via MIR21 [105]. Both the expression and functional loss of STAT1 are related to the development of mammary adenocarcinomas [106].…”
Section: Mir21mentioning
confidence: 99%